Endoscopic third Ventriculostomy for Malfunction of Ventriculoperitoneal Shunt; Our Experience - Rahman, Md Moshiur; Khan, Robert Ahmed; Rahman, Md Mahmudur; Ziauddin, Md; Chowdhury, Muhtamim; Ahammed, Md Bashir; Khan, SIM Khairun Nabi; Hasan, Md Motasimul (Bangladesh Journal of Neurosurgery, 2023)
Background: Ventriculoperitoneal (VP) shunt is a common procedure for treating hydrocephalus of various causes. Malfunction of VP shunt like obstruction, infection etc. are encountered with revision surgeries which may not have favourable outcome. Endoscopic third ventriculostomy (ETV) in such cases is challenging, and can be salvageable in appropriate cases. Objective: Aim of the study is to analyze the role of endoscopic third ventriculostomy as an alternative to shunt revision for malfunctioning and infected ventriculoperitoneal (VP) shunts. Method: We report 54 cases from 2012 to 2018 in private setup, retrospectively we analysed in all ages including children and adults. Minimum follow up period was 2 years. Results: In 2 cases we did ETV twice and in 1 case of thalamic glioma where the patient was shunt dependent probably due to post radiotherapy adhesion ETV was successful. The success rate of ETV was 88.9% in our study. Conclusion: Success rate of ETV depends on various factors and careful selection of patients; CSF infection and communicating hydrocephalus are of poor prognosis. ETV is the feasible alternative for the treatment of failed VP shunt cases in non-communicating hydrocephalus. Bang. J Neurosurgery 2022; 12(1): 20-23